Aspectos clínicos e anatomopatológicos do embolismo neoplásico em cães submetidos à necropsia em Santa Maria, RS - Molozzi, Helenize (2023)
Neoplastic embolism (NE) is a phenomenon in which individual and/or clustered neoplastic cells (neoplastic emboli) circulate in the patient's bloodstream. This syndrome is a well-established cause of death in human oncology patients. Despite the increasing prevalence of neoplasms in dogs in recent decades, this phenomenon is underexplored in this and other animal species. The objective of this study is to characterize the clinical and anatomical pathological findings of NE in dogs submitted to necropsy at the Laboratório de Patologia Veterinária (LPV) of the Universidade Federal de Santa Maria (UFSM). To this end, necropsy reports of dogs (2008-2022) at the LPV were reviewed. Cases in which death or euthanasia was related to malignant neoplasms were separated, and among them, those containing histological descriptions of intravascular (blood) neoplastic emboli were included as cases of NE. Data related to the clinical history, type of neoplasm involved, macroscopic and histological findings were analyzed. Formalin-fixed tissues were subjected to new cuts for histological reevaluation. NE was identified in 31 of 528 (5.9%) dogs whose cause of death or reason for euthanasia was attributed to a malignant neoplasm, with mammary neoplasms being the most frequently involved (18 [58.1%]). In six dogs (6/31 [19.4%]), NE was considered the major necropsy finding. In seven dogs, the embolism was considered severe but not the primary necropsy finding. In the remaining patients (19/31 [58%]), NE was considered mild to moderate and was considered a secondary finding in the necropsy. The clinical evolution of the six dogs in which NE was the primary necropsy finding ranged from minutes to 21 days, and the main clinical signs were anorexia (4/6) and dyspnea (3/6). NE was most prevalent in the lungs (25/31), kidneys (9/31), adrenal glands (5/31), and brain (5/31). As for macroscopic findings, only one dog showed a macroscopic neoplastic embolus. The lungs were macroscopically described as consolidated (9/25), heavy (8/25), and with hemorrhages (8/25). Hemorrhages were also observed in the myocardium (4/5), kidneys (2/5), adrenal glands (2/5), and brain (2/5). Histologically, the most common consequences in the organs of dogs with NE were hemorrhage (18/31), thrombosis (11/31), edema (8/31), infarctions (7/31), and intimal proliferation with perivascular fibrosis (4/31). The findings of this study suggest that NE may be an underdiagnosed entity in veterinary practice. It is hoped that this work will help spread knowledge about this phenomenon, increasing the chances of clinical suspicion and ante-mortem diagnosis.